ANALISIS PERMASALAHAN SISWA DALAM MENGIKUTI PEMBELAJARAN BIOLOGI DI SMA NEGERI 1 ULUNOYO - Yuliana Ndruru (TUNAS : Jurnal Pendidikan Biologi, 2024)
The aims of this research were (1) to know the problems of students in joining the Biology learning in SMA Negeri 1 Ulunoyo. And (2) to know the factors cause students’ problems in joining the Biology learning in SMA Negeri 1 Ulunoyo. Based on the research finding that the students’ problems in joining the Biology learning namely; the students did not have the competence in comprehending the Biology learning theoretically and practically, the Biology materials cannot be understood because they contain the Science language, Latin language, and the Chemistry unsure, the students did not active in learning activity, they did not have motivation to study, they did not spirit to study, and they did not have the enthusiasm in joining the process of learning activity. Then, the factor cause of students’ problems in joining the Biology learning namely; the tool and facilities and infrastructure as support the Biology learning are incomplete and inadequate. One of them namely; the equipment of nature science laboratory, the learning media and the learning source in Biology learning so they influence the teacher’s ability in teaching the learning materials and they can influence the students’ motivation to study. The, as the suggestions were proposed by the researcher namely; the results of this research expected can be the evaluation for the teacher and students and to be used as reference in improving the learning system. For the teacher, expected improve the learning strategy and method to trigger the students’ motivation and intention in joining the Biology learning. For the students, expected can be improving the motivation and intention in learning the Biology learning material.